Covid‐19 pandemic and the skin - Drenovska, Kossara (Int J Dermatol, 2020)
In the beginning of the COVID‐19 outbreak, skin manifestations, if present, were not paid enough attention. Then, the focus moved toward the impact of the prolonged use of personal protective measures in both healthcare workers and patients. In the meantime, attention is increasingly paid to dermatology as a result of the concern for certain groups of dermatologic patients, including those whose condition may worsen by the thorough disinfection measures and those treated with immunosuppressants or immunomodulators. Following patients with psoriasis on biological therapy, as well as other inflammatory and autoimmune cutaneous disorders such as atopic dermatitis, pemphigus, pemphigoid diseases, and skin cancer provoked the interest of dermatologists. Finally, an intriguing question to the dermatologic society was whether skin changes during COVID‐19 infection exist and what could be their diagnostic or prognostic value. Here, we summarize skin conditions during the COVID‐19 pandemic, patient information, and expert recommendations and give an overview about the registries launched to document skin changes during COVID‐19, as well as details about certain patient groups infected with SARS‐CoV‐2, for example, psoriasis, atopic dermatitis, and autoimmune bullous diseases.